2005
DOI: 10.1097/01.ede.0000147116.34813.56
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Short-Term Fine-Particulate Matter Exposure and Onset of Myocardial Infarction

Abstract: Although a very small effect cannot be excluded, there was no consistent association between ambient levels of fine-particulate matter and risk of MI onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 34 publications
1
93
2
4
Order By: Relevance
“…103 Several studies have also found positive associations between elevated PM or traffic exposures over a period as brief as a few hours 109 -111 or a few days and an elevated risk for MI (Table 5). 13,110,[112][113][114][115] In general, acute increases in risk for ischemic heart disease events have been observed consistently, even as rapidly as 1 to 2 hours after exposure to elevated PM, in case-crossover analyses. 109 -111 Other studies have reported an increased risk for MI shortly after exposure to traffic.…”
Section: Specific Cardiovascular Events/conditionsmentioning
confidence: 97%
“…103 Several studies have also found positive associations between elevated PM or traffic exposures over a period as brief as a few hours 109 -111 or a few days and an elevated risk for MI (Table 5). 13,110,[112][113][114][115] In general, acute increases in risk for ischemic heart disease events have been observed consistently, even as rapidly as 1 to 2 hours after exposure to elevated PM, in case-crossover analyses. 109 -111 Other studies have reported an increased risk for MI shortly after exposure to traffic.…”
Section: Specific Cardiovascular Events/conditionsmentioning
confidence: 97%
“…A study from Rome, Italy, reported increased risk of MI associated with PM pollution, especially during warm periods, 261 but a study from King County, WA, observed no PM-MI associations. 262 In a much larger case-crossover study using data from 21 U.S. cities with Ͼ300,000 MI events, a 20-g/m 3 increase in PM 10 ambient concentration was associated with a 1.3% (95% CI, 0.6%-2%) increased risk of MI. 263,264 …”
Section: Short-term Exposure and Cardiovascularmentioning
confidence: 97%
“…Smaller studies on cardiovascular morbidity end-points generally found little evidence for effects on sudden cardiac arrest [57], myocardial infarction [58], heart rate variability [59], and measures of systemic inflammation or thrombosis [60].…”
Section: Epidemiologymentioning
confidence: 99%